1987
DOI: 10.1073/pnas.84.18.6563
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor necrosis factor expression and resistance in a human breast tumor cell line.

Abstract: Tumor necrosis factor (TNF) is a polypeptide cytokine that is cytotoxic to some but not all tumor cells. The basis for resistance to the cytotoxic effects of this agent remains unclear. We have studied the development of TNF resistance in human ZR-75-1 breast carcinoma cells. ZR-75-1 cells have undetectable levels of TNF RNA and protein. However, TNF transcripts are transiently induced in these cells by exposure to recombinant human TNF. This induction of TNF RNA is associated with production of TNF-like prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 24 publications
0
45
0
2
Order By: Relevance
“…Moreover, cells transfected with TNF exhibited enhanced invasive capacity in nude mice, an effect that could be neutralized with antibodies to TNF (21 ). Other groups have shown that certain human tumor cell lines express TNF in vitro and that prolonged exposure to TNF led to the development of resistance to the cytotoxic effects ofTNF and induced constitutive secretion ofTNF by these cells (22).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, cells transfected with TNF exhibited enhanced invasive capacity in nude mice, an effect that could be neutralized with antibodies to TNF (21 ). Other groups have shown that certain human tumor cell lines express TNF in vitro and that prolonged exposure to TNF led to the development of resistance to the cytotoxic effects ofTNF and induced constitutive secretion ofTNF by these cells (22).…”
Section: Introductionmentioning
confidence: 97%
“…has been shown to mediate cleavage of both pro-TNF and pro-TGF␣ (40 -42). It has been reported that exposure of mammary cancer cells to TNF treatment stimulates the synthesis and release of soluble TNF and that this is associated with resistance to TNF cytotoxicity (43). The shedding of the p75 TNF receptor (TNFR2), which is also mediated by TNF-converting enzyme, is stimulated by TNF as well (44,45).…”
Section: Fig 8 the Metalloprotease Inhibitor Batimastat Modulates Tmentioning
confidence: 99%
“…IL-1 and TNF, the prominent monocyte/macrophage products can be produced by a variety of tumour cell lines (Busson et al, 1987;Beutler & Cerami, 1986;Spriggs et al, 1987;Dinarello, 1988). Elevated circulating levels of TNF and IL-1 have been found in patients suffering chronic infection, parasitic and malignant diseases (Beutler & Cerami, 1986;Dinarello, 1988;Moldawer et al, 1988).…”
Section: +26 -23mentioning
confidence: 99%